BATAK TOBA LANGUAGE KINSHIP - Hayulina Manurung, Yayuk; Sari Siregar, Fatimah; Dharmawati, Dharmawati; Arda, Mutia; Bismala, Lila (RADJA PUBLIKA, 2022)
This study aims to analyze how the kinship system of the Toba Batak language is compared to the proto language. This research is a quantitative descriptive study using lexicostatistical and glottochronological techniques. This study explains and describes the kinship of the proto language with the Toba Batak language. The kinship of these two languages will be studied using comparative historical linguistic studies. The data in this study were 200 Swadesh vocabularies spoken by each informant. The result of this research is that the Proto language (PAN) and the Toba Batak language have a kinship level of 56.5%. Where in it there are pairs of identical words recorded as many as 33 pairs. or as much as 29% and then 30% of word pairs that have sound correspondence both phonemic and phonetically and have the same meaning from the total data that have word pairs and 46 word pairs or 41% of word pairs that have one different phoneme.